Podstawowe założenia metody graficzno-porównawczej stosowanej w ramach badań pismoznawczych w Polsce - Zieniewicz, Iwona (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The present paper is devoted to one of the methods of handwriting research, i.e. The comparative-graphic method which — owing to its versatility — is the most frequently applied in experts’ opinion-making practice. The reflections included in the text cover the issues regarding, above all, the basic assumptions of this method, requirements concerning the examined material, the course of research, experts’ problems with the criteria to draw final conclusions, as well as the difficulties faced by handwriting experts, resulting from the specific character of examined material which heavily relies on the psychophysical properties of the author of the handwriting, causing fluctuations in some circumstances, which in turn may impede the research and conclusion process.The present publication is primarily addressed to practitioners, i.e. persons who — for professional reasons — appoint handwriting experts, and evaluate the opinions issued by such experts, meaning the broadly understood judicial bodies. It can also serve as a teaching aid for students attending forensic, criminal or civil procedure courses.
Keywords: badanie pisma ręcznego; ekspertyza; opinia; materiał porównawczy; cechy identyfikacyjne pisma ręcznego; wartość diagnostyczna opinii piśmienniczej